O envolvimento da comunidade rural de Cássia dos Coqueiros (São Paulo, Brasil) em programas de saúde The engagement of the rural community of Cassia dos Coqueiros County (S. Paulo State, Brazil) in health programs - Nagib Haddad; Jarbas Leite Nogueira (Revista de Saúde Pública, 1973)
Apresenta-se trabalho realizado no município de Cássia dos Coqueiros, (São Paulo, Brasil), para envolvimento da comunidade em programas de saúde, através da criação de uma entidade associativa, congregando lideres naturais, a ela atribuindo-se responsabilidades na execução de algumas tarefas comunitárias desses programas. Comentam-se os resultados alcançados no desenvolvimento de programas de educação sanitária, de uma campanha para construção de fossas secas, na qual a entidade associativa responsabilizou-se pela sua execução; e na melhoria de relacionamento e freqüência da população ao atendimento do posto médico local. The engagement of the rural community of Cassia dos Coqueiros (S. Paulo State, Brazil) in health programs with the creation of an association entity congregating people with leadership is presented. Responsibilities for execution of some community tasks of these programs were given to the partnership. The results achieved in the development of health education programs are commented. A program of construction of pit privies was developed on the sponsorship of the association entity with good results. Improvement of the frequency of health examination and of the relationship of the people with the local health center is also commented.